An Updated Review on MSMD Research Globally and A Literature Review on the Molecular Findings, Clinical Manifestations, and Treatment Approaches in China - Xia, Lu; Liu, Xu-Hui; Yuan, Yuan; Lowrie, Douglas B.; Fan, Xiao-Yong; Li, Tao; Hu, Zhi-Dong; Lu, Shui-Hua (Frontiers in Immunology, 2022)
Mendelian susceptibility to mycobacterial disease (MSMD) arises from a group of rare inherited errors of immunity that result in selective susceptibility of otherwise healthy people to clinical disease caused by low virulence strains of mycobacteria, such as Mycobacterium bovis Bacille Calmette-Guérin (BCG) and environmental mycobacteria. Patients have normal resistance to other pathogens and no overt abnormalities in routine immunological and hematological evaluations for primary immunodeficiencies. At least 19 genes and 34 clinical phenotypes have been identified in MSMD. However, there have been no systematic reports on the clinical characteristics and genetic backgrounds of MSMD in China. In this review, on the one hand, we summarize an update findings on molecular defects and immunological mechanisms in the field of MSMD research globally. On the other hand, we undertook a systematic review of PubMed (MEDLINE), the Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science, EMBASE, CNKI, and Wanfang to identify articles published before Jan 23, 2022, to summarize the clinical characteristics, diagnosis, treatment, and prognosis of MSMD in China. All the English and Chinese publications were searched without any restriction on article types.